Evaluation of Central Auditory Processing of Azeri-Persian Bilinguals Using Dichotic - Fatahi, Jamileh; Tahaei, Ali Akbar; Ashayeri, Hassan; Mohammadkhani, Ghassem; Jalaie, Shohreh (Iranian Journal of Child Neurology, 2019)
Objectives: Sometimes there is no hearing impairment, but it is possible to have an auditory disorder. This is known as a central auditory processing disorder (CAPD). Verbal dichotic tasks are useful tools to evaluate CAPD, but there is almost no tool to assess this for Azeri people in their native language. The aim of this study is to evaluate central auditory processing of Azeri participants by Azeri dichotic digit test (ADDT). Materials & Methods: Participants were 52 normal Iranian Azeri students (mean age 23.27± 4.71 ; 26 female, 26 male).They were chosen by convenient sampling. ADDT was constructed and administered in free recall format along with a Persian dichotic digit test (PDDT). After two to four weeks, reliability was performed. Results: The mean of the right ear score of PDDT and ADDT were 98.90 and 99.09 percent, respectively. ADDT was reliable in almost all scores. There was no significant difference in performance between men and women in any score of both tests (p>0.05). The results showed a significant difference between both ears’ scores in PDDT (p<0.02) as well as in ADDT (p=0.00). The right ear advantage were seen in both tests. Conclusions: All participants performed significantly better on numbers presented in the right ear than the left ear in both tests. Central auditory processing of Azeri participants for Azeri is similar to that for Persian.